Iodine and thyroid function - Hye Rim Chung (Korean Society of Pediatric Endocrinology, 2014)
Severe iodine deficiency causes hypothyroidism that results in impaired somatic growth and motor development in children. Mild and moderate iodine deficiencies cause multifocal autonomous growth of thyroid, which results in thyrotoxicosis. On the other hand, iodine excess is associated with the development of hypothyroidism and thyroid autoimmunity. In areas of iodine deficiency, a sudden increase in iodine intake is associated with transient hyperthyroidism. Recent studies demonstrated that long-term thyroid function of subjects who experienced both iodine deficiency and iodine excess during childhood tended to be abnormal despite optimization of their current iodine intake. Iodine status in the Korean Peninsula is very unique because people in the Republic of Korea have been shown to have predominantly excessive iodine levels, whereas the Democratic People's Republic of Korea is known to be an iodine-deficient area. Further research is warranted to verify the optimal ranges of iodine intake and to clarify the effects of iodine intake on thyroid disorders in the Korean Peninsula.